The role of guanine nucleotides in protein biosynthesis. - Kurland, C G (1978)
It is not possible to select one competing substrate molecule over another one when the selection system is at equilibrium. Therefore, it is convenient to view all substrate selections as transport phenomena. The requirement for a displacement from equilibrium to effect a substrate selection can be met in different ways. One particularly convenient way is to drive a nonselected substrate, such as GTP in protein synthesis, far from equilibrium. This allows the flux of selected substrate to be relatively slow, but effectively irreversible. Accordingly, the conventional view that GTP hydrolysis drives protein synthesis is amended. It is suggested that the regeneration GTP from GDP is the driving force for protein synthesis. Several different selection mechanisms are described in the context fof systems driven by displacements from equilibrium of the nonselected substrate. These are then evaluated in light of recent experimental results. The data argue against the relevance of proofreading mechanisms for aminoacyl-tRNA selection by the messenger RNA-programmed ribosome. Similarly, recent data suggesting that the translation of messenger RNA is not dependent on the presence of elongation factors and guanine nucleotides are reevaluated.